Progress toward an integrated understanding of Parkinson's disease [version 1; referees: 2 approved] - Maxime W.C. Rousseaux; Joshua M. Shulman; Joseph Jankovic (F1000Research, 2017)
Parkinson's disease (PD) is the second most common neurodegenerative disorder after Alzheimer's disease, affecting over 10 million individuals worldwide. While numerous effective symptomatic treatments are currently available, no curative or disease-modifying therapies exist. An integrated, comprehensive understanding of PD pathogenic mechanisms will likely address this unmet clinical need. Here, we highlight recent progress in PD research with an emphasis on promising translational findings, including (i) advances in our understanding of disease susceptibility, (ii) improved knowledge of cellular dysfunction, and (iii) insights into mechanisms of spread and propagation of PD pathology. We emphasize connections between these previously disparate strands of PD research and the development of an emerging systems-level understanding that will enable the next generation of PD therapeutics.